Antarctic ice-free terrestrial microbial functional redundancy in core ecological functions and microhabitat-specific microbial taxa and adaptive strategy - Mimi Zhang; Yao Xiao; Qianqian Song; Zhiyong Li (Environmental Microbiome)
Abstract Background Although ice-free terrestrial ecosystems in Antarctica cover only limited areas, they harbor diverse and metabolically active microbial communities. These ecosystems encompass distinct microhabitats such as mosses, lichens, and soils, each offering unique ecological niches. However, how different microbial taxa respond to microhabitat heterogeneity, ecological strategies such as functional redundancy and specialization contribute to adaptation in extreme environments remains underexplored. To address these questions, we employed high-throughput 16 S rRNA gene and ITS sequencing in combination with GeoChip-based functional gene profiling to assess the structure and functional potential of microbial communities across moss, lichen and soil microhabitats in Antarctic ice-free terrestrial ecosystem. Results Microhabitat type has a greater influence on microbial community structure and function in the ice-free Antarctic terrestrial ecosystem than geographical location. Though all prokaryotic communities were dominated by Pseudomonadota, Nostoc and Endobacter were significantly enriched in the moss and lichen microhabitats, respectively. Meanwhile, all fungal communities were primarily dominated by Ascomycota and Basidiomycota, with Byssoloma and Usnea showing significant enrichment in the moss and lichen microhabitats, respectively. Despite these taxonomic differences, the three microhabitats show similar core ecological functions with widespread microbial functional redundancy. Nevertheless, clear microhabitat-specific functional specialization was suggested. For example, moss microhabitat was enriched in Pyoverdin_pvcC and Zeaxanthin_glucosyltransferase, sdhA, lichen microhabitat harbored higher levels of nhaA, nikC, vacuolar_iron_transport, mttB, glucoamylase, pel_Cdeg, pme_Cdeg, rgh, rgl, while soil microhabitat was enriched in 5f1_ppn and isopullulanase. Notably, genes involved in carotenoid biosynthesis were significantly more abundant in moss and lichen microhabitats than in soil microhabitat, indicating the adaptive capacity of symbiotic microorganisms to mitigate ultraviolet radiation and oxidative stress to protect their hosts. Conclusions Microbial communities associated with distinct microhabitats (i.e. mosses, lichens, and soils) in Antarctic ice-free terrestrial ecosystem exhibit both functional redundancy in core ecological functions and microhabitat-specific specialization in key microbial taxa and adaptive strategy.